ETOS KERJA PEREMPUAN PENAMBANG PASIR DALAM MEMBANTU MENINGKATKAN KESEJAHTERAAN KELUARGA (Studi di Kelurahan Ulunggolaka Kecamatan Latambaga Kabupaten Kolaka) - Apriani, Iin; Roslan, Suharty; Tawulo, Megawati Asrul (Universitas Halu Oleo, 2020)
This study aims to determine the work ethics of women in the sand miners to help improve family welfare, and to find out the factors that influence the work ethics of women in the sand miners to help improve welfare. Family. This research method uses qualitative research methods with data collection techniques used are interviews, observation and documentation, data sources used are primary and secondary data sources, data analysis in this study is done with qualitative description and then analysis in accordance with power capabilities the researcher’s reason to help the researcher's conclusions. The results showed that: the work ethic possessed by women sand miners, namely: a timely attitude in which a trait or ability possessed by a person or woman who mines sand, honesty means there is a matching of words with conscience and with reality or reality, an attitude of willingness to cooperate the attitude where the individuals concerned have the same interests and awareness, and the simplicity of where to live and focus on what is really needed. As for the factors that influence the work ethic of women sand miners in Kelurahan Ulunggolaka: Religion is a value that will influence or determine the lifestyle of its adherents, Culture in which regulates so that each individual understands what must be done and to regulate human behavior in interaction , Environmental conditions which include the condition of natural resources such as land, water and where can also be interpreted into everything that is around humans, and as for the Economic Structure which is used to show the composition or composition of the economic sector in an economy. Also helps to improve family welfare where the work is done by women sand miners to meet the needs of family life.